Optimization of dye adsorption using FeO nanoparticles encapsulated with alginate beads by Taguchi method - Heydar Rezaei; Masoud Haghshenasfard; Ahmad Moheb (Adsorption Science & Technology)
Adsorption of methylene blue from synthetic wastewater using Fe 3 O 4 nanoparticles encapsulated with alginate beads is carried out. The adsorption experiments were conducted in a continuous column equipped with an external magnetic field. The effects of important factors such as initial dye concentration, dose of Fe 3 O 4 in beads, adsorption time, and intensity of magnetic field on the Methylene blue (MB) adsorption have been studied experimentally. The Taguchi method is applied for optimization of operating conditions in dye adsorption onto the magnetic alginate beads. The variance analysis showed that the adsorption time is most effective factors by higher contribution percent in dye adsorption. The optimum conditions are achieved as 20 mg l −1 dye concentration, 1 Gy dose of Fe 3 O 4 in beads, 60 min of adsorption time, and 440 G of magnetic field intensity. The equilibrium adsorption data were analyzed using isotherm models and results revealed that the experimental data are in agreement with Freundlich isotherm model and the kinetic analyses showed that the adsorption kinetics was described accurately by pseudo-first-order model.